Impact of fresh and fermented vegetable consumption on gut microbiota and body composition: insights from diverse data analysis approaches - Pihelgas, Susan; Ehala-Aleksejev, Kristel; Kutti, Mari-Liis; Kuldjärv, Rain; Kazantseva, Jekaterina (Frontiers in Nutrition, 2025)
BackgroundThe impact of fermented foods on human health, particularly through gut microbiota, is a widely discussed topic. However, the number of nutritional studies demonstrating their health benefits remains limited. This study evaluated the effects of fermented vegetables (FVs) intake including fermented carrots, kohlrabi, and kimchi on human health parameters, with a primary focus on gut microbiota. In addition to microbiota analysis, we assessed anthropometric parameters, stool frequency, and data from nutritional diaries. A total of 65 volunteers were recruited, of whom 55 completed the study. FVs are valuable health products, combining dietary fibers and lactic acid bacteria, both essential for supporting normal gut microbiota. To better understand the effects of FV consumption in different populations, participants were divided into three groups: controls without reported health problems (CTRL), individuals with constipation (CONS), and those recovering from an antibiotic course (AB). Multiple analytical approaches were applied to evaluate: (1) the effects of FV consumption within the three focus groups, (2) the response of different gut enterotypes to a three-week FV consumption period based on taxonomic hierarchical analyses, and (3) the combined effects across the entire cohort.ResultsThe choice of analyzed groups was crucial for interpreting the results, revealing varied effects depending on the context. Overall, the findings showed that consuming FVs modified gut microbiota composition, increasing the abundance of butyrate-producing and anti-inflammatory bacterial species. Additionally, phase angle, a key indicator of cellular health reflecting cell integrity and hydration, showed statistically significant improvement across the cohort, indicating better metabolic health after the intervention. Food diaries further revealed a reduction in sugar consumption among participants, highlighting an additional benefit of enriching diets with fermented foods.ConclusionsThese results demonstrate the clear positive impact of FV consumption on human health, particularly through gut microbiota modulation and metabolic improvements.